2016
DOI: 10.1038/srep28843
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observations of lithium battery reactions—operando neutron diffraction analysis during practical operation

Abstract: Among the energy storage devices for applications in electric vehicles and stationary uses, lithium batteries typically deliver high performance. However, there is still a missing link between the engineering developments for large-scale batteries and the fundamental science of each battery component. Elucidating reaction mechanisms under practical operation is crucial for future battery technology. Here, we report an operando diffraction technique that uses high-intensity neutrons to detect reactions in non-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 40 publications
14
85
0
Order By: Relevance
“…Custom‐designed cell types for in operando NPD measurements can be summarized as the flat‐plate design with a single electrode/separator/electrode layer, the prismatic design with several stacked layers,4b,16a–c,e,45,49,61a,b,d,e the cylindrical type containing rolled layers,8,16d,23,25,29,43,50,51,56,58,61c,62,64 and the confined electrode type where the beam predominantly illustrates the electrode of interest ( Figure ).…”
Section: Experimental Aspects Of In Operando Neutron Powder Diffractimentioning
confidence: 99%
See 1 more Smart Citation
“…Custom‐designed cell types for in operando NPD measurements can be summarized as the flat‐plate design with a single electrode/separator/electrode layer, the prismatic design with several stacked layers,4b,16a–c,e,45,49,61a,b,d,e the cylindrical type containing rolled layers,8,16d,23,25,29,43,50,51,56,58,61c,62,64 and the confined electrode type where the beam predominantly illustrates the electrode of interest ( Figure ).…”
Section: Experimental Aspects Of In Operando Neutron Powder Diffractimentioning
confidence: 99%
“…Cylindrical Rolled Layer Cell : The cylindrical rolled layer cell contains an electrode and separator roll inserted into a cylindrical can, such as in the commercial 18650 cell, where the relatively large amount of active materials yields intense data despite the hydrogen in the electrolyte and separators . Custom cells have been made using cans composed of aluminum, quartz, nickel‐plated steel,62a and vanadium 61c,62b–e.…”
Section: Experimental Aspects Of In Operando Neutron Powder Diffractimentioning
confidence: 99%
“…Moreover, people expect fast-charging batteries at a similar refueling speed as in the gasoline car. However, in a previous neutron diffraction study, it was reported that inhomogeneous reactions occur in the graphite-negative electrode at a high-speed charge-discharge rate [1]. These inhomogeneous reactions are related to the degradation of the battery performance; furthermore, they carry some great risks.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a line-shape of the Compton scattered energy spectrum, called the Compton profile, is obtained from this incoherent scattering technique and depends on the element. Here, the Compton profile, J(p z ), is shown in the following equation [6], J(p z ) = ρ(p)dp x dp y (1) where ρ(p) is the electron momentum density, p = (p x , p y , p z ) is the momentum, and p z is assumed to lie along the direction of the scattering vector. The ρ(p) is expressed by the following [7,8],…”
Section: Introductionmentioning
confidence: 99%
“…The full-scale usage of SPICA has just begun. The first battery study on the structure dependence of the charge-discharge rate was published in 2016 [84]. SPICA will be used to carry out experiments on material science and observe structural changes in practical devices under an operative condition.…”
Section: Special Environment Powder Diffractometer Spicamentioning
confidence: 99%